Type I-E* CRISPR-Cas of Klebsiella pneumoniae upregulates bacterial virulence by targeting endogenous histidine utilization system - Jieying Li; Yuxiao Liu; Jingsi Jiang; Fang Chen; Nan Zhang; Xun Kang; Lin Liu; Yingjuan Wang; Qianfeng Xia; Chuanlong Zhu; Dai Kuang (mSphere, 2025)
ABSTRACT Klebsiella pneumoniae is a globally recognized microbial pathogen with significant clinical impact. The bacterium harbors the clustered regularly interspaced short palindromic repeats (CRISPR)-Cas systems, which provide adaptive immunity against invading foreign nucleic acids. Recent studies suggest that certain CRISPR-Cas systems can regulate endogenous genes, influencing bacterial virulence. However, their role in regulating pathogenicity in K. pneumoniae remains poorly understood. This study investigates the regulatory role of the type I-E* CRISPR-Cas system in a hypervirulent K. pneumoniae strain, focusing on its impact on histidine metabolism and pathogenicity. Transcriptome analyses identified differentially expressed genes (DEGs) between the casABECD-deletion and wild-type strains, including significant upregulation of the histidine utilization (Hut) operon and downregulation of biofilm-related genes. These molecular changes resulted in enhanced histidine metabolic activity, reduced biofilm formation, attenuated virulence in A549 lung epithelial cells, and improved survival of Galleria mellonella, as validated through phenotypic and virulence assays. Our bioinformatic analysis indicated that the CRISPR-Cas system in K. pneumoniae targets the hutT sequence, which is part of the Hut operon. Furthermore, the overexpression of hutT mitigated CRISPR-Cas-mediated repression of the Hut operon, as observed in virulence assays, while simultaneous deletion of hutH and casABECD restored the reduced virulence in the ΔcasABECD strain. Additionally, deletion of casABECD significantly enhances the growth of the strain in medium with histidine as the sole carbon source, highlighting the intricate regulatory role of the CRISPR-Cas system in metabolic adaptation. Collectively, these findings uncover a novel role for the CRISPR-Cas system in regulating metabolic pathways and virulence in hypervirulent K. pneumoniae.IMPORTANCEClustered regularly interspaced short palindromic repeats (CRISPR)-Cas systems are primarily recognized for their roles in adaptive immunity against foreign genetic elements in bacteria. However, emerging evidence indicates that these systems can also regulate endogenous genes, thereby influencing bacterial physiology and virulence. In this study, we demonstrate that the type I-E* CRISPR-Cas system in Klebsiella pneumoniae targets the hutT gene, a critical component of the histidine utilization (Hut) pathway. This targeting potentially impacts hutT transcription and alters the expression of other hut genes, ultimately enhancing bacterial virulence. Our findings reveal a previously unrecognized regulatory mechanism through which CRISPR-Cas systems facilitate metabolic adaptation and pathogenicity in K. pneumoniae. This study broadens our understanding of the multifaceted roles of CRISPR-Cas systems in bacterial physiology and pathobiology, with implications for clinically relevant pathogens.